FORMULATION AND EVALUATION OF COLON TARGETED DRUG DELIVERY SYSTEM OF MESALAMINE - Sanjay Shahurao Popale; Asmita Tarkase; Ashok A. Chopane; Pratiksha A. Shinde; Abhijeet B. Thorat; Afroj A. Shaikh; Dr. Manisha Zaware; Rajiya A. Khan; Swati D. Bankar (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Conventional drug delivery systems for treating colon disorders, such as inflammatory bowel diseases, infections, and colon cancer, often fail due to insufficient drug concentrations reaching the targeted site. Therefore, the development of effective, site-specific drug delivery systems presents a significant challenge in pharmaceutical technology. A major obstacle is the premature absorption or degradation of active ingredients in the upper gastrointestinal (GI) tract, which must be addressed for successful colonic drug delivery. Mesalamine, a drug commonly used to treat ulcerative colitis, has a half-life of 5-7 hours, is water-insoluble, and exhibits low oral bioavailability (20-30%). This study aimed to develop colon-targeted matrix tablets of Mesalamine using xanthan gum and guar gum to improve drug release in the colon. The tablets were evaluated for hardness, friability, weight variation, drug content uniformity, swelling index, and in-vitro drug dissolution. FT-IR analysis confirmed no interactions among the drug, polymers, and excipients. A 3² factorial design was employed to assess the effects of varying amounts of xanthan and guar gum on formulation characteristics. Rheological properties, including bulk and tapped densities, compressibility index, Hausner’s ratio, and angle of repose, were also measured. Tablets were compressed using a 10-station R&D tablet press with 13 mm flat-faced punches and further evaluated for physicochemical properties and drug release profile using USP Type I dissolution apparatus at 50 rpm. Simulated colonic conditions were maintained during in-vitro release studies, and stability testing was conducted at 40°C/75% RH for 180 days. Statistical analysis indicated that formulation variables significantly influenced matrix integrity and drug release (P < 0.05). Formulation F3, which demonstrated optimal release characteristics, was selected for long-term stability studies. Results showed no significant changes in drug content or dissolution profiles, confirming the stability of the formulation.